Environmental Exposures and Asthma Development: Autophagy, Mitophagy, and Cellular Senescence - Sachdeva, Karan; Do, Danh C.; Zhang, Yan; Hu, Xinyue; Chen, Jingsi; Gao, Peisong (Frontiers in Immunology, 2019)
EEnvironmental pollutants and allergens induce oxidative stress and mitochondrial dysfunction, leading to key features of allergic asthma. Dysregulations in autophagy, mitophagy, and cellular senescence have been associated with environmental pollutant and allergen-induced oxidative stress, mitochondrial dysfunction, secretion of multiple inflammatory proteins, and subsequently development of asthma. Particularly, particulate matter 2.5 (PM2.5) has been reported to induce autophagy in the bronchial epithelial cells through activation of AMP-activated protein kinase (AMPK), drive mitophagy through activating PTEN-induced kinase 1(PINK1)/Parkin pathway, and induce cell cycle arrest and senescence. Intriguingly, allergens, including ovalbumin (OVA), alternaria alternata, and cockroach allergen, have also been shown to induce autophagy through activation of different signaling pathways. Additionally, mitochondrial dysfunction can induce cell senescence due to excessive ROS production, which affects airway diseases. Although autophagy and senescence share similar properties, recent studies suggest that autophagy can either accelerate the development of senescence or prevent senescence. Thus, in this review, we evaluated the literature regarding the basic cellular processes, including autophagy, mitophagy, and cellular senescence, explored their molecular mechanisms in the regulation of the initiation and downstream signaling. Especially, we highlighted their involvement in environmental pollutant/allergen-induced major phenotypic changes of asthma such as airway inflammation and remodelling and reviewed novel and critical research areas for future studies. Ultimately, understanding the regulatory mechanisms of autophagy, mitophagy, and cellular senescence may allow for the development of new therapeutic targets for asthma.